Primary productivity of the phytoplankton in a tropical Brazilian shallow lake: experiments in the lake and in mesocosms - Feresin,Eliana Garcia (2010)
AIM: To evaluate the primary productivity of the phytoplankton in the Lake Monte Alegre, southeastern Brazil, and the factors that influence its fluctuations, experiments were carried out in the lake and in mesocosm; METHODS: Primary productivity rates were measured using the 14C technique, in experiments carried out monthly in the lake, during one year, and in two mesocosm experiments, one in the winter and another in the summer. Other factors also analyzed were temperature, dissolved oxygen, pH, electrical conductivity, chlorophyll-a, alkalinity, nutrients, and nitrogen limitation. Hypotheses on the influence of grazing and excretion by zooplankton and fish on phytoplankton properties were tested in two mesocosm experiments; RESULTS: Higher PP in the water column of the lake occurred in the transition periods, when thermal stratification is unstable, and lower PP in the cool season (frequent mixing) and in mid-summer (more stable stratification). The limiting factor in the cool season seems to be mainly temperature and in mid-summer lower light intensities, due to higher rainfall and overcast, N limitation and physical disturbances caused by storms. PP was not influenced by the zooplankton in the experiment I, despite the effect of grazing on other phytoplankton properties. The excretion by the phytoplanktivorous fish (adults of Tilapia rendalli) enhanced PP in the experiment II, outweighing grazing on the phytoplankton; CONCLUSIONS: We suppose that the preponderant factors which affected primary productivity in the lake were physical and chemical ones, biotic factors having a secondary role. The thermal behavior of the lake, which is warm discontinuous polymictic, governs nutrient losses and releases, influencing PP in addition to other factors related to seasons.